Poverty of Women and the Covid-19 Pandemic in Indonesia - Irwan Gani (Budapest International Research and Critics University, 2021)
Poverty for women is a picture where women experience limitations, the inability to fulfill their basic needs properly. Pandemic conditions that cause changes in behavior to limit all social activities to prevent transmission. By using a reference study supported by secondary data, this research aims to describe, explain and analyze poverty among women during the pandemic, then produce ideas on how to solve the problem of poverty in women. The results of this reference study found that poverty that occurs in women is caused by restrictions on social activity behavior in the community, resulting in a decrease in income in the family which impacts on women's poverty. Women are a vulnerable group to survive the Covid-19 pandemic without the support of adequate facilities and skills in mastering information technology, so women find it difficult to build and produce a creative economy. Even though during the Covid-19 pandemic, creative economy players were able to survive the downturn in economic conditions. Women are more susceptible to being poor. Conscious efforts are needed in these women to get up and add skills in mastering technology in building a creative economy.